KÓPLIKLER TEORIYASÍNÍŃ BAZÍ BIR QOLLANÍLÍWLARÍ - Tanirbergenov, S.A.; Berdieva, Z.İ. (SCIENCE and SOCIETY, 2022)
The article discusses the practical application of set theory. It analyses the methods of the applicating set theory in programming languages.